Publication cultures and the citation impact of open access - Thomas Eger; Armin Mertens; Marc Scheufen (Managerial and Decision Economics, 2021)
Does open access (OA) to journal articles foster citations to these articles? We compare the citation impact of gold and green OA in two disciplines: Biology and Economics & Management. The empirical analysis covers all articles of these disciplines included in the Web of Science “Journal Citation Reports” between 2000 and 2019. We show that, controlling for confounding variables pertaining to the journals and articles, gold OA increases citations across all articles. However, the individual disciplines feature starkly different effects: a 18.3% increase in Biology, compared to a decrease by 30.9% in Economics & Management. Also Green OA leads to an increase in citations to academic research. These results are confirmed by a number of robustness checks.
Keywords: 650